Direct aqueous solution synthesis of an ultra-fine amorphous nickel–boron alloy with superior pseudocapacitive performance for advanced asymmetric supercapacitors. (28th June 2017) - Li, Wei; Wang, Shaolan; Wu, Ming; Wang, Xiangjian; Long, Yi; Lou, Xiaojie
Abstract : This study reports a facile aqueous solution synthesis of an ultrafine amorphous nickel–boron alloy and its applications as a novel positive electrode material for asymmetric supercapacitors. Abstract : This study reports a facile aqueous solution synthesis of an ultrafine amorphous nickel–boron alloy and its applications as a novel positive electrode material for asymmetric supercapacitors. The electrochemical properties of the as-prepared amorphous Ni–B alloy were studied, and the results demonstrate that the material synthesized at room temperature shows a high specific capacitance of 2230 F g −1 at 1 A g −1 in a three-electrode system, and the capacitance remained at 986 F g −1 when the current density is increased up to 20 A g −1 . An amorphous Ni–B//AC (activated carbon) asymmetric supercapacitor is successfully assembled with the amorphous Ni–B alloy as the cathode and AC as the anode. Such an assembled device shows a high specific capacitance of 135.5 F g −1 at 1 A g −1 . It can deliver a maximum energy density of 59.3 W h kg −1 at a power density of 1004 W kg −1, better than most of the supercapacitors reported in the literature. Furthermore, this asymmetric supercapacitor also exhibits an excellent, long cycle life along with 88.2% specific capacitance retention after 5000 consecutive cycles. Our results show that the amorphous nickel–boron alloy, as a new type of high-performance electrode material, is promising for advanced supercapacitor applications.